2004
DOI: 10.1024/0036-7281.146.4.159
|View full text |Cite
|
Sign up to set email alerts
|

The humoral and cellular immune response of sheep against Borna disease virus in endemic and non-endemic areas

Abstract: Borna Disease (BD) is a mostly fatal disease of horses and sheep endemic in central Europe. Antibodies to Borna disease virus (BDV) have been described in sheep and other species living in BD non-endemic areas. Meaningful clinical BDV serology is hampered by difficulties in defining serological cut-offs, which require the investigation of populations from endemic areas. Here we studied BD serology in sheep from endemic and non-endemic areas of similar geography in Switzerland. Antibodies to BDV antigens were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…The data in the present study show that, similar to what has been found with bornavirus infection in mammals, 25,27,28 there is considerable variation in the nature and titer of antibodies formed in psittacines naturally infected by bornavirus. The varying antibody titers for different bornaviral proteins may reflect different immunological responses of individual birds to the proteins, but different relative amounts of bornaviral proteins in the infected birds giving rise to different antibody titers cannot be excluded.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The data in the present study show that, similar to what has been found with bornavirus infection in mammals, 25,27,28 there is considerable variation in the nature and titer of antibodies formed in psittacines naturally infected by bornavirus. The varying antibody titers for different bornaviral proteins may reflect different immunological responses of individual birds to the proteins, but different relative amounts of bornaviral proteins in the infected birds giving rise to different antibody titers cannot be excluded.…”
Section: Discussionsupporting
confidence: 87%
“…These findings may bear some relationship with findings in sheep and cats where variable levels of anti-P40 and -P24 antibodies as well as animals with Borna disease without the presence of anti-bornaviral antibodies have been described. 25,27,28 Finally, the presence of birds without evidence of bornavirus infection, such as the 11 green-cheeked conures in a collection of heavily infected psittaciformes, suggests that there may be variation in susceptibility to bornavirus infection among different, even closely related, psittacine species. However, little is currently known about the role of various environmental factors in ABV infection, such as effects of humidity, temperature etc.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is no significant amount of virus present in amniotic fluids or placental tissues (Li et al, 2004). The rise in MCF incidence during lambing season as shown in epidemiological studies (Muller-Doblies et al, 2001a) is probably unrelated to the parturition process itself but rather due to other factors such as the higher levels of virus shedding provo-ked by stress at high stocking densities, and the in creased numbers of sheep coming into contact with MCF susceptible species.…”
Section: Discussionmentioning
confidence: 99%
“…In endemic areas in Germany (Bavaria), the incidence dropped down to about 0.02–0.04% in the 1990s (Herden et al., ). Thus, the incidence of clinical BD is relatively low, with less than 100 affected horses or sheep per year in endemic areas (Herzog et al., ; Dürrwald and Ludwig, ; Caplazi et al., ; Staeheli et al., ; Muller‐Doblies et al., ; Dürrwald et al., ; Richt et al., ; Kistler et al., ). Seasonally, there is an increase of clinical cases in spring and early summer and secular rhythm has also been observed with disease peaks every 3–5 years.…”
Section: Assessmentmentioning
confidence: 99%